Transient diplopia secondary to dental anesthesia. A case report - de Oliveira, Leandro Benetti [UNESP] (2016)
Intraoral administration of local anesthetics is one of the most common dental procedures. Although this procedure is well known for its safety, complications can still occur. A 17-year-old female patient developed transient diplopia and ipsilateral lateral rectus muscle paralysis following administration of local anesthesia for right maxillary third molar extraction. The patient was informed and proper instructions were given regarding the complications. Complete resolution occurred within 2 h. In this article, we review the clinical examination and management of this uncommon occurrence.